OPTIMALISASI PERAN POLRI DALAM PENANGANAN KONFLIK ANTAR ORGANISASI KEMASYARAKATAN - Wildhan Indra Pramono; Arthur Josias Simon Runturambi (Jurnal Litbang Polri, 2020)
Community organizations in Indonesia have a presence in the community to be a counterweight, where government work is overseen by the association. For the community, social organizations can be used as a forum to convey their aspirations. The objectives of the social organization are often interpreted differently by its members, especially when the social organization is used as a tool for interests. If not noticed, various existing social organizations, especially youth, have the potential to be a tool to legalize the existence of thuggery. Conflicts between social organizations occur and recur is caused by the economy (unemployment, youth, and seizure of territory). The police facilitate mediation to settle in a peaceful manner by calling on each hostile party to meet and always be accompanied by the police. The police intelligence is very important in providing early detection, especially in anticipating disruption of kamtibmas that can occur at any time that does not know the time and place. The situation of Kamtibmas and crime has a tendency to increase from year to year in line with the development of various aspects of community life, meanwhile a conducive security and order situation is absolute, to realize in order to support the implementation of national development including the running of the wheels of government and the nation's economy. Keyword: mass organizations, conflicts, National Police Intelligence Agency